Col-OSSOS: Evidence for a Compositional Gradient Inherited from the Protoplanetary Disk? - Michaël Marsset; Wesley C. Fraser; Megan E. Schwamb; Laura E. Buchanan; Rosemary E. Pike; Kathryn Volk; Nuno Peixinho; Susan Benecchi; Michele T. Bannister; Nicole J. Tan; J. J. Kavelaars (The Planetary Science Journal, 2023)
In the present-day Kuiper Belt, the number of compositional classes and the orbital distributions of these classes hold important cosmogonic implications for the solar system. The Colours of the Outer Solar System Origins Survey (Col-OSSOS) recently showed that the observed color distribution of small ( H ⪆ 6) trans-Neptunian objects (TNOs) can be accounted for by the existence of only two composition classes, named BrightIR and FaintIR, where the range of colors in each class can be modeled as mixtures of two material end-members. Here, we combine the high-precision photometric measurements of Col-OSSOS with those of previous surveys to investigate the orbital distribution of the two color classes and reinterpret the known color–inclination correlation of TNOs in the context of the BrightIR/FaintIR taxonomy. In addition to confirming the previously reported distinct orbital distributions of these classes, we identify a trend of increasing orbital inclinations toward the bluer end of the optical and near-infrared color distribution of BrightIR objects. Using the output of numerical simulations investigating the orbital evolution of TNOs during their scattering phase with Neptune, we show that this trend could reflect a composition gradient in the early protoplanetary disk, in the range of heliocentric distances over which TNOs from the BrightIR class accreted. However, tensions between this interpretation and the existence of blue contaminants among cold classical TNOs, and possible alternative origins for the detected correlation, currently bear uncertainty on our proposed interpretation.